Efektivitas Penggunaan Strategi Quick On The Draw Dalam Pembelajaran IPS Sub-Sub Tema Keunggulan Iklim Indonesia pada peserta didik kelas VIII SMPN 1Surakarta Tahun Ajaran 2015/2016 - Hadiid Wijayanto, Perdana; , Dra. Siti Taurat Aly,M.Pd (2016)
This research was motivated by the problems in the learning process of students in class who are still using conventional methods (lectures),So the use of learning strategies quick on the drow in the classroom is needed so students are more kretif and akfit to create a classroom atmosphere that is more interesting and fun.This research includes quantitative study using learning strategies quick on the drow.The purpose of this study was to determine the effectiveness of learning strategiesquick on the drow compared to the conventional methods on the material superiority Indonesian climate class VIII SMP N 1 Surakarta.This research method is using a type of experimental research using about Pre Test - Post Test. There are two classes of two classes in this research is the experimental class using the learning strategies quick on the drow and grade control using conventional methods (lectures). Population of in this study is a class VIII SMP N 1 Surakarta consisting of 8 classes with the number of 163 students. Total sample in this study is 64 students. Techniques in this study using a convenience sampling sampling (sampling potluck of the highest rated class VIII), This research concluded that the control class has a value of Post Test average of 87.74% when compared to post test experimental group increased after getting treatment by using the learning strategies quick on the drow in learning activities in the classroom with an average value of 94.04% thus the value of the average post test experimental class is higher because it has a difference of 6.26% compared with the average value of grade control. Conclusion learning strategies quick on the drow be more effectively used in learning.